IMPLEMENTASI APRAISAL DALAM EVALUASI BAHASA: SEBUAH ANCANGAN WACANA FORENSIK - Panggabean, Sarma; Lestari, Febrika Dwi (Universitas Papua, 2017)
The aim of this research are (1) describing language evaluation on studentsâ article on attitude (2) describing language evaluation on studentsâ article on engagement (3) describing language evaluation on studentsâ article on graduation. The research method used in this research is descriptive qualitative that is done by concordance method analysis and distribution by using a software of Simple Concordance Program (SCP). The data for this research is an article text written by the students of Indonesia department. The result shows that (1) the inclination of using lexis 0f negative attitude that is showed on negative affect, value, and appreciation by the students. (2) the inclination of using lexis of negative graduation by the students through writing the domination of metaphor in the phenomenon happened in society. (3) the system of appraisal in the article written by the students is graduation ^ engagement ^ attitude. This result showed because the writers of an article mostly use the function of language to strengthen and weaken the attitude and engagement related to the text inwriting their article.